CONDITIONED REINFORCEMENT IN CHAIN SCHEDULES WHEN TIME TO REINFORCEMENT IS HELD CONSTANT1. Issue 2 (14th January 2013) - Bell, Matthew C.; Williams, Ben A.
Abstract Two alternative approaches describe determinants of responding to a stimulus temporally distant from primary reinforcement. One emphasizes the temporal relation of each stimulus to the primary reinforcer, with relative proximity of the stimulus determining response rate. A contrasting view emphasizes immediate consequences of responding to the stimulus, the key factor being the conditioned reinforcement value of those immediate consequences. To contrast these approaches, 4 pigeons were exposed to a two‐component multiple schedule with three‐link chain schedules in each component. Only middle‐link stimuli differed between chains. Baseline reinforcement probabilities were 0.50 for both chains; during discrimination phases it was 1.0 for one chain and 0.0 for the other. During discrimination phases pigeons responded more to the reinforcement‐correlated middle link than to the extinction‐correlated middle link, demonstrating that responding was affected by the probability change. Terminal link responding was also higher in the reinforced chain, even though the terminal link stimulus was identical in both chains. Of greatest interest is initial link responding, which was temporally most distant from reinforcement. Initial link responding, necessarily equal in the two chains, was significantly higher during the 1.0/0.0 discrimination phases, even though overall reinforcement probability remained constant. For 3 of 4 birds, in fact, initial‐link response rates were higher than terminal‐link response rates, an outcome that can be ascribed only to the potent conditioned reinforcement properties of the middle‐link stimulus during the discrimination phases. Results are incompatible with any account of chain behavior based solely on relative time to reinforcement.